40 GASTROINTESTINAL SYMPTOMS AND SEIZURES IN AUTISTIC REGRESSION. Issue 1 (1st January 2007) - Angkustsiri, K.; Hansen, R. L.; Ozonoff, S.; Krakowiak, P.; Jones, C.; Deprey, L. J.; Croen, L. A.; Hertz-Picciotto, I.
Abstract : Purpose: Developmental regression as a distinct subgroup within the autistic spectrum has yet to be completely understood. Prior studies have suggested an increase in gastrointestinal symptoms and seizures with regression, whereas others have not. The purpose of this study is to examine the presence of associated medical problems such as gastrointestinal complaints and clinical seizures in a population-based sample of children with autism and regression (REG), children with autism without regression (NREG), and typically developing children in the general population (GP). Methods: Children between the ages of 2 and 5 years were recruited through a larger population study, the CHARGE study. The diagnosis of autism or autistic spectrum disorder was confirmed with scores from the Autism Diagnostic Interview-Revised (ADI-R) and Autism Diagnostic Observation Schedule (ADOS), yielding 210 subjects. Of those, 87 (41%) had regression as defined by loss of either language or social skills as measured by the ADI-R. The NREG group consisted of 123 children whose parents gave no history of language or social skills loss. One hundred seventeen children recruited from the same catchment area constituted the GP control group. GI symptoms and seizure history were obtained through clinical interview and ADI-R responses. Results: Constipation was described in 16% of NREG, 11% of REG, and 3% of GP. History of seizure was present in 10% of NREG, 6% of REG, and 1% of GP. After adjusting for age and sex, there were significant differences in the frequency of reported constipation between both autism groups and GP. No significant differences were found in the frequency of abdominal pain, gaseousness, or diarrhea. History of seizures was significantly higher in NREG compared to GP. Conclusion: Children with autism, regardless of pattern of onset, were more likely to report constipation, but no other gastrointestinal symptoms, compared with the control group. Only children with autism without regression were more likely than controls to have a history of seizures.